Two Decades of Biodiesel Research from Waste Cooking Oil: A Bibliometric and Literature Review of Heterogeneous Catalysts - Suherman Suherman; Muharnif Muharnif; Ilmi Abdullah; Arridina Susan Silitonga; Marnida Yusfiani; Wan Azmi Wan Hamzah (Universitas Muhammadiyah Magelang, 2025)
Waste cooking oil (WCO) represents an abundant yet underutilised feedstock for biodiesel production, constrained primarily by challenges related to catalyst performance and recyclability. Conventional homogeneous catalysts, such as sodium hydroxide (NaOH) and potassium hydroxide (KOH), often suffer from deactivation after several reuse cycles due to leaching and sensitivity to impurities. In contrast, heterogeneous catalysts, including calcium oxide (CaO) and biomass-derived materials, offer promising, reusable, and environmentally benign alternatives for WCO-based biodiesel synthesis. This study presents a comprehensive bibliometric and literature review examining global research trends in biodiesel production from WCO using heterogeneous catalysts. As environmental concerns and fossil fuel depletion intensify, biodiesel has gained increasing attention as a sustainable and renewable energy substitute. A total of 974 publications indexed in the Scopus database between 2006 and June 2024 were systematically analysed to identify key research trends, influential authors, geographical distribution, and thematic clusters. Data retrieved from the Scopus database were exported in RIS format and subsequently processed using VOSviewer for bibliometric visualisation. Keyword analysis revealed dominant clusters around “WCO biodiesel” and “heterogeneous catalysts”, encompassing research topics such as transesterification, oxidation stability, performance optimisation, and corrosion behaviour. The bibliometric mapping highlights strong interconnections among research themes, particularly those associated with catalysts, transesterification mechanisms, engine performance, and emission reduction. The literature review further evaluates various types of heterogeneous catalysts including CaO, biochar, and metal- and biomass-based catalysts focusing on their synthesis routes, physicochemical properties, and optimal operating conditions. Research productivity on WCO biodiesel peaked during 2020”“2021 but declined after 2022, suggesting research saturation or shifting interest toward emerging renewable technologies. Co-country analysis identified India and Malaysia as leading contributors, while Tabatabaei et al. and Bae et al. were the most prolific authors. This study offers a holistic overview of research progress and future directions, providing valuable insights for advancing cleaner, more efficient, and sustainable biodiesel production technologies.